2004
DOI: 10.1111/j.1365-2842.2004.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of fixed partial denture replacement

Abstract: The purpose of this study was to investigate, by means of the finite element method the mechanical behaviour of three designs of fixed partial denture (FPD) for the replacement of the maxillary first premolar in shortened dental arch therapy. Two-dimensional, linear, static finite element analyses were carried out to investigate the biomechanics of the FPDs and their supporting structures under different scenarios of occlusal loading. Displacement and stress distribution for each design of FPD were examined, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
(15 reference statements)
2
26
0
Order By: Relevance
“…Stress concentration usually exists in the connector of the CFPD, which is consistent with the findings of most scholars (Wang et al, 1998;Romeed et al, 2004). So it is advisable for clinicians to pay attention to the design of the connector of the abutment near to the pontic.…”
Section: Discussionsupporting
confidence: 77%
“…Stress concentration usually exists in the connector of the CFPD, which is consistent with the findings of most scholars (Wang et al, 1998;Romeed et al, 2004). So it is advisable for clinicians to pay attention to the design of the connector of the abutment near to the pontic.…”
Section: Discussionsupporting
confidence: 77%
“…Romeed et al. (17) stated that it is necessary to ensure that the greatest value of principal stress in all materials be less than the relevant critical value to rule out any possibility of material failure. Kamposiora et al.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the sophistication of the FEA analyses, Romeed et al. (17) believe that the analyses suffer some limitations: materials are assumed to be isotropic, homogeneous, and linear elastic, despite the anisotropic nature of some structures and the presence of voids or cracks. Although the FE analyses allow the introduction of these parameters, the correct information about them for all tooth parts and all dental materials is not available.…”
Section: Discussionmentioning
confidence: 99%
“…But if the K t is appreciable, the maximum stress is substantially larger than σ nom and the estimated d min required to achieve 20 years of clinical function is insufficient. Of note, several 2D and 3D finite element studies have identified that "high" stress concentrations develop at the connector area [4,5,[8][9][10][11][12][13]]. Yet, no study has provided a quantitative description of the magnitude of K t in terms of the bridge geometry.…”
Section: Theoretical Backgroundmentioning
confidence: 99%